Perancangan Sistem Informasi Pendaftaran Magang Berbasis Web Pada PT Perkebunan Nusantara IV Regional I - Dwi Hafizah Akbar; Abdullah Umar Muzammil; Tudi Firmanto (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
Information technology has become a key element in improving operational efficiency and data management in various sectors. PT Perkebunan Nusantara IV Regional I, which is one of the companies operating in the plantation sector, utilizes this technology to optimize its internal processes. One of the company's main concerns is the internship program, which was previously managed manually, giving rise to various problems, including time inefficiency, high costs, and difficulties for prospective participants in monitoring their registration status. This research seeks to create a web-based information system designed to streamline the internship registration process, enhance efficiency, and alleviate the administrative load on the company. The method used in this approach is the waterfall method, which includes requirements analysis, design, implementation, testing and maintenance. Data was obtained through direct observation, interviews with employees, and literature study. This system was designed using PHP and the Laravel framework, as well as MySQL as the database system. The results of this research show that this information system speeds up the internship registration process, allows prospective participants to register and monitor their status online, and helps companies manage data in a structured and accurate way.